SOCIAL DATA ANALYSIS USING BIG-DATA ANALYTIC TECHNOLOGIESAPACHE FLUME, HDFS, HIVE. - Panigrahi, Ms.Sulochana; Kumar, Dr.S Mohan (IJRDO -Journal of Computer Science Engineering, 2016)
Analysis on Social media data is difficult due to language that is used forcomments. For this analysis using Hive and its queries to give the sentiment data based up on thegroups that defined in the HQL (Hive Query Language) is utmost important and so much indemand. The analysis can be positive, moderate and negative comments. Tools can be used to dothe analysis are: Apache Flume, HDFS, Hive. In this paper all related research works and BigdataTools, technologies and observations from the survey are all presented for betterunderstanding.